EFEK INTERAKSI SIFAT MACHIAVELLIAN DAN LOCUS OF CONTROL INTERNAL TERHADAP PERILAKU DISFUNGSIONAL AUDITOR - Paul Usmany; Muhammad F. Laitupa (Soso-Q : Jurnal Manajemen, 2017)
This study aims to examine the effect of machiavellian, locus of control, and to examine the effect of locus of control on the relationship of machiavellian properties with auditor dysfunctional behavior. Respondent is the auditor of BPK RI representative of Maluku Province 42 people and all of them are used as sample in this research. Number of Auditors in BPK RI Representatives of Maluku Province amounted to 42 people but from questionnaires distributed as many as 42 questionnaires, only 35 questionnaires were returned. The method used is Partial Least Squares Method (PLS).The result obtained is that Machiavellian properties have a positive effect on auditor dysfunctional behavior. Locus of control positively affects auditor dysfunctional behavior. Locus of control affects the relationship of machiavellian properties and auditor dysfunctional behavior. This is indicated by the influence of time budget pressure on the relationship between machiavellian properties and auditor dysfunctional behavior is negative